Personality and the Expression of Symptomatology in Schizophrenia and Bipolar Disorder. Issue 11 (November 2019) - Urošević, Snežana; Halverson, Tate; Sponheim, Scott R.
Abstract : Abstract: Researchers and clinicians have begun using dimensions rather than categories to classify psychopathology with a reliance on personality questionnaires to tap traits that can inform dimensional characterizations. A neglected concern is whether in severe psychopathology questionnaire-based assessments of personality reflect a lifetime propensity toward a diagnosis, as some personality-psychopathology models posit, or reflect the transient effects of current symptoms, as a complication model of personality-psychopathology would suggest. Accurate characterization of psychopathology is necessary to understand etiology and prescribe clinical care. We studied 127 adults with schizophrenia, schizoaffective, or bipolar disorder who completed well-validated measures of personality, current symptomatology, and lifetime psychopathology. We found that normative personality traits were related to current symptoms but unrelated to lifetime symptomatology, whereas the schizotypal trait of cognitive-perceptual distortions predicted lifetime psychosis severity. Questionnaire-based assessments of normative personality are likely affected by current symptom states and may fail to yield a stable characterization of psychopathology. Abstract : Supplemental digital content is available in the text.